Expected benefits and concerns regarding virtual reality in caring for terminally ill cancer patients – a qualitative interview study - Anja Greinacher; Bernd Alt-Epping; Christina Gerlach; Cornelia Wrzus (BMC Palliative Care)
Abstract Background Many palliative cancer patients require inpatient hospital treatment for medical reasons, which contrasts their frequent desire to be at home. Virtual reality (VR) could be a way of bringing the home environment closer to them. First observations have shown benefits from VR for inpatients in palliative care. The aim of this qualitative, descriptive study was to explore the expectations of in-patients suffering from incurable cancer and their relatives about VR, in particular individualized VR images of the patients’ own home. Methods Semi-structured interviews with inpatients suffering from incurable cancers and their relatives in three medical settings (palliative care, hematology, radiotherapy) of a German university hospital. Qualitative content analysis about expected benefits and concerns regarding VR-videos showing their private home; defining the main topics deductively and the subcategories inductively. We also assessed the patients’ subjective perspective on their remaining time to live to estimate the impact of double awareness on the results. The Patient Advisory Board informed the study protocol and conduct. Results We interviewed 15 patients (8 men; age M = 63.4, SD = 11.34; range 39–82) under palliative care, and four relatives. We organized the interview content in 6 themes (general interest, desired content, non-desired content, expected benefits, concerns, and irregularities) and 26 sub-themes. Most patients and relatives were interested in using VR during hospital treatment. They often preferred viewing nature or tourist sites over seeing their home or family. Reasons could be linked to privacy concerns and the general desire for distraction from the current situation that they specified with their expectation of well-being, a break from the patient-experience, the pursue of curiosity, and the VR evoking fond memories. Conclusion VR seems to be of interest for palliative cancer patients, especially as distraction and relief from their illness. The desired content can be very different, so a choice from a selection of VR-content should be made available. If patients want to see videos of their own home, recordings by relatives instead of study or hospital staff seem to meet the need for privacy. Trial registration Registered at Deutsches Register Klinischer Studien; registration number: DRKS00032172; registration date: 11/07/2023. https://drks.de/search/de/trial/DRKS00032172.